Neurologic Complications Associated with Sjögren's Disease: Case Reports and Modern Pathogenic Dilemma. (5th August 2014) - Colaci, Michele; Cassone, Giulia; Manfredi, Andreina; Sebastiani, Marco; Giuggioli, Dilia; Ferri, Clodoveo
Abstract : Objectives . Sjögren's syndrome (SS) may be complicated by some neurological manifestations, generally sensory polyneuropathy. Furthermore, involvement of cranial nerves was described as rare complications of SS. Methods . We reported 2 cases: the first one was a 40-year-old woman who developed neuritis of the left optic nerve as presenting symptom few years before the diagnosis of SS; the second was a 54-year-old woman who presented a paralysis of the right phrenic nerve 7 years after the SS onset. An exhaustive review of the literature on patients with cranial or phrenic nerve involvements was also carried out. Results . To the best of our knowledge, our second case represents the first observation of SS-associated phrenic nerve mononeuritis, while optic neuritis represents the most frequent cranial nerve involvement detectable in this connective tissue disease. Trigeminal neuropathy is also frequently reported, whereas neuritis involving the other cranial nerves is quite rare. Conclusions . Cranial nerve injury is a harmful complication of SS, even if less commonly recorded compared to peripheral neuropathy. Neurological manifestations may precede the clinical onset of SS; therefore, in patients with apparently isolated cranial nerve involvement, a correct diagnosis of the underlying SS is often delayed or overlooked entirely; in these instances, standard clinicoserological assessment is recommendable.